Efficacy and safety of trabectedin for patients with unresectable and relapsed soft‐tissue sarcoma in Japan: A Japanese Musculoskeletal Oncology Group study. Issue 6 (11th December 2019) - Kobayashi, Hiroshi; Iwata, Shintaro; Wakamatsu, Toru; Hayakawa, Keiko; Yonemoto, Tsukasa; Wasa, Junji; Oka, Hiroyuki; Ueda, Takafumi; Tanaka, Sakae
Abstract : Background: Although initial trabectedin (1.2 mg/m 2 ) is safe and effective for patients with translocation‐related sarcoma (TRS) in Japan, its efficacy in other types of soft‐tissue sarcomas (STSs) remains unknown. This study retrospectively investigated its efficacy and safety through postmarketing surveillance of trabectedin in patients with unresectable and relapsed STS. Methods: One hundred forty patients received intravenous trabectedin (1.2 mg/m 2 on day 1 every 21 days) over the course of 24 hours. The primary endpoint was the efficacy and safety of trabectedin. Results: Grade 3 or higher adverse events occurred in 100 patients (71%) and included hepatotoxicity (37.8%), neutropenia (32.8%), and rhabdomyolysis (3.6%). Patients at high risk for grade 3 or higher rhabdomyolysis (36%) were classified by height (≥170.3 cm) and age (≤32 years) through a classification and regression tree model (area under the curve, 0.9). The overall median progression‐free survival (PFS) was 3.7 months; with respect to the histological type, the median PFS was 17.4 months for myxoid liposarcoma, 4.9 months for leiomyosarcoma, 5.6 months for synovial sarcoma, and 3.7 months for dedifferentiated liposarcoma. Histological type (liposarcoma/leiomyosarcoma [L‐sarcoma] and TRS) and grade 3 neutropenia (but not grade 4) were associated with significantly improved PFS after trabectedin treatment ( P  = .003, P  = .04, and P  = .001). The median growth modulation index (GMI) was 0.91; 37 patients (36.7%) experienced a GMI > 1.33, and among patients with solitary fibrous tumors and undifferentiated pleomorphic sarcoma, 60% and 42.9%, respectively, had a GMI > 1.33. The median overall survival (OS) was 16.4 months. A GMI > 1.33 was associated with significantly improved OS ( P  = .0006). Conclusions: Initial trabectedin at 1.2 mg/m 2 has clinically meaningful benefits for patients with L‐sarcoma and certain histological subtypes of TRS. Abstract : At an initial dose of 1.2 mg/m 2 (applied only in Japan), trabectedin has clinically meaningful benefits for patients with liposarcomas/leiomyosarcomas and translocation‐related sarcomas (especially myxoid liposarcomas, synovial sarcomas, and solitary fibrous tumors among translocation‐related sarcomas). The safety profile is comparable and dose reduction is less common in comparison with previous phase 2 and 3 clinical trials, and younger age and higher stature are associated with a high risk of rhabdomyolysis induced by trabectedin.